Effect of Formulation of Edible Coating Solution on Weight Loss of Kaempferia Galanga Peeled Tubers - Ridawati, Ridawati; Alsuhendra, Alsuhendra (Fakultas Pariwisata dan Perhotelan Universitas Negeri Padang, 2023)
Kaemferia galanga L. (Kencur) is a spice plant used for household purposes and traditional medicine. It contains phytochemical compounds. It has high water content; it caused the shelf life of peeled K. galanga at room temperature to be relatively short. There are no studies that report the effect of glycerol concentration and immersion time in edible coating based on mocaf flour on the quality of peeled K. galanga. This research aimed to study the effect of immersion time of peeled K. galanga tubers in edible coating solution with different glycerol concentrations and storage time on weight loss and sensory characteristics of K. galanga peeled tubers. The results of the descriptive test on the sensory aspect showed that the external appearance of K. galanga changed to a very dry, very hard texture, and reduced aroma during storage. RAL test showed a significant effect on the concentration of immersion time and storage time on the weight loss of peeled galangal (Sig. < 0.05). The interaction between the variables showed a significant effect on the weight loss of peeled K. galanga. The immersion time for 2 minutes showed a significant difference. Duncan's test showed 5% glycerol concentration showed the most significant results in kept weight loss compared to other concentrations.